Variability in the Reporting of Baseline Characteristics, Treatment, and Outcomes in Esophageal Atresia Publications: A Systematic Review - Teunissen, Nadine; Brendel, Julia; Eaton, Simon; Hall, Nigel; Thursfield, Rebecca; van Heurn, Ernest L.W.; Ure, Benno; Wijnen, Rene (European Journal of Pediatric Surgery, 2023)
Introduction As survival rates of infants born with esophageal atresia (EA) have improved considerably, research interests are shifting from viability to morbidity and longer-term outcomes. This review aims to identify all parameters studied in recent EA research and determine variability in their reporting, utilization, and definition.Materials and Methods Following PRISMA guidelines, we performed a systematic review of literature regarding the main EA care process, published between 2015 and 2021, combining the search term “esophageal atresia” with “morbidity,” “mortality,” “survival,” “outcome,” or “complication.” Described outcomes were extracted from included publications, along with study and baseline characteristics.Results From 209 publications that met the inclusion criteria, 731 studied parameters were extracted and categorized into patient characteristics (n = 128), treatment and care process characteristics (n = 338), and outcomes (n = 265). Ninety-two of these were reported in more than 5% of included publications. Most frequently reported characteristics were sex (85%), EA type (74%), and repair type (60%). Most frequently reported outcomes were anastomotic stricture (72%), anastomotic leakage (68%), and mortality (66%).Conclusion This study demonstrates considerable heterogeneity of studied parameters in EA research, emphasizing the need for standardized reporting to compare results of EA research. Additionally, the identified items may help develop an informed, evidence-based consensus on outcome measurement in esophageal atresia research and standardized data collection in registries or clinical audits, thereby enabling benchmarking and comparing care between centers, regions, and countries.
Keywords: esophageal atresia; outcome; characteristics